2019
DOI: 10.1096/fj.201900077r
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin reduces renal damage associated with rhabdomyolysis by decreasing ferroptosis‐mediated cell death

Abstract: Acute kidney injury is a common complication of rhabdomyolysis. A better understanding of this syndrome may be useful to identify novel therapeutic targets because there is no specific treatment so far. Ferroptosis is an iron‐dependent form of regulated nonapoptotic cell death that is involved in renal injury. In this study, we investigated whether ferroptosis is associated with rhabdomyolysis‐mediated renal damage, and we studied the therapeutic effect of curcumin, a powerful antioxidant with renoprotective p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
130
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 192 publications
(139 citation statements)
references
References 61 publications
9
130
0
Order By: Relevance
“…Ramesh G et al have reported that cisplatin could induce both apoptosis and necrosis which is mediated by TNF receptor 2 (TNFR2) in mice AKI model 17 . In recent years, researches have showed that ferroptosis is playing an emerging role in clinical AKI as well as rodent models induced by IRI and rhabdomyolysis 18,19 . Earlier before two decades, Baliga et al's work has suggested the importance of ferric ion in pathological processes of cisplatin induced renal injury in mice 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Ramesh G et al have reported that cisplatin could induce both apoptosis and necrosis which is mediated by TNF receptor 2 (TNFR2) in mice AKI model 17 . In recent years, researches have showed that ferroptosis is playing an emerging role in clinical AKI as well as rodent models induced by IRI and rhabdomyolysis 18,19 . Earlier before two decades, Baliga et al's work has suggested the importance of ferric ion in pathological processes of cisplatin induced renal injury in mice 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Ischemia/reperfusion renal injury is the leading cause of ARF, a disease with high morbidity and mortality because of the lack of effective treatment 9 , 38 . Renal tubular cell death induced by I/R was considered as the main cause of ARF 19 , 46 . In the present study, we confirmed the occurrence of I/R-induced ferroptosis in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Acyl-CoA synthetase long-chain family member 4 (ACSL4) dictates ferroptosis sensitivity by shaping cellular lipid composition 18 . Recent studies have revealed that ferroptosis plays an important role in rhabdomyolysis-associated renal damage and severe acute pancreatitis (SAP) induced acute kidney injury 19 , 20 . Ferroptosis mediates postischemic and toxic renal necrosis, which may be therapeutically targeted by ferrostatins 21 , indicating that ferroptosis may play central roles in the pathogenesis of renal I/R injury.…”
Section: Introductionmentioning
confidence: 99%
“…Following polymer and/ or linker degradation, the drug is then released to the cytosol 45 . Of note, lysosomal cathepsins are involved in lysosome-mediated apoptosis in several pathological processes including renal diseases and AKI, and, as recently reported, in ferroptosis 49,50 . Moreover, previous studies have revealed that curcumin restrains the leakage of hydrolases by an effect that depends on the lysosomal membrane stabilization 51 .…”
Section: Discussionmentioning
confidence: 61%